The invention of custom : natural law and the law of nations, ca. 1550-1750 - Iurlaro, Francesca (Oxford : Oxford University Press, 2021)
This text tells the neglected story of the relationship between custom and the European natural law and ius gentium tradition. It explores what cultural values and practices facilitated the emergence of custom and rendered it into as a source of the law of nations, and how they did so.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from PDF title page (viewed on March 7, 2022).
Keywords: Customary law -- History; Natural law -- History; Customary law -- Europe -- History; Customary law, International; International law